Projecting wheat demand in China and India for 2030 and 2050: Implications for food security - Mottaleb, Khondoker Abdul; Kruseman, Gideon; Frija, Aymen; Sonder, Kai; Lopez-Ridaura, Santiago (Frontiers in Nutrition, 2023)
Applying the time series econometric estimation procedure, this study projected the per capita and annual aggregate wheat consumptions of China and India during 2019-2050. This study found that the yearly per capita wheat consumption of China will increase from 65.8 kg in 2019 to 68.5 kg in 2030, and 70.6 kg in 2050. In India, the yearly per capita wheat consumption will increase to 73.3 kg in 2030 and 96.2 kg in 2050 from 60.4 kg in 2019. In 2019, the aggregate wheat consumption in China was 96.4 million ton and in India it was 82.5 million ton. Considering the projected population growth rates under low-fertility assumptions, aggregate wheat consumption of China will increase by more than 13% in 2030 and by 28% in 2050. Under the high-fertility rate assumption, however the aggregate wheat consumption of China will increase by 18% in 2030 and nearly 50% in 2050. In the case of India, under both low and high-fertility rate assumptions, aggregate wheat demand in India will increase by 32-38% in 2030 and by 70-104% in 2050 compared to 2019 level of consumption. The combined populations of China and India were 2.78 billion in 2020, representing 36% of the world population (7.75 billion), and their inhabitants consumed 35.5% of the world’s wheat that year. Our results underline the importance of wheat in both countries, which are the world’s top wheat producers and consumers, and suggest the importance of research and development investments to maintain sufficient national wheat grain production levels to meet China and India’s domestic demand. This is critical both to ensure the food security of this large segment of the world populace, which also includes 23% of the total population of the world who live on less than US $1.90/day, as well as to avoid potential grain market destabilization and price hikes that arise in the event of large import demands.